[tex]x^{3}+6x^{2}+10x + 3 = 0\\\\x^{3}+3x^{2}+x+3x^{2}+9x+3 = 0\\\\x(x^{2}+3x+1) + 3(x^{2}+3x+1) = 0\\\\(x+3)(x^{2}+3x+1+x^{2}+3x+1) = 0\\\\(x+3)(2x^{2}+6x+2) = 0\\\\2(x+3)(x^{2}+3x+1) = 0 \ \ /:2\\\\(x+3)(x^{2}+3x+1) =0\\\\x+3 = 0\\\\x = -3\\\\lub\\\\x^{2}+3x+1 = 0\\\\\Delta = b^{2}-4ac = 3^{2}-4\cdot1\cdot1 = 9-4 = 5\\\\\sqrt{\Delta} = \sqrt{5}\\\\x = \frac{-3-\sqrt{5}}{2} \ \ \vee \ \ x = \frac{-3+\sqrt{5}}{2}\\\\x = -3 \ \ \vee \ \ x = \frac{-3-\sqrt{5}}{2} \ \ \vee \ \ x = \frac{-3+\sqrt{5}}{2}[/tex]